Climate Change Induced Major Livelihood Changes on Char Dwellers in Northern Regions of Bangladesh (SAARC Journal of Agriculture, 2022)
Bangladesh is one of the most vulnerable to climate change due to its geographic position and socio-economic context. The newly emerged land in the river channel is called char. The northern region especially Lalmonirhat, Kurigram, Gaibandha is most vulnerable. The study was carried out based on a questionnaire interview, focus group discussion, and secondary data sources from Bangladesh Meteorological Department (BMD). Climatic factors such as temperature (seasonal Tmax and Tmini, daily average Tmax and Tmini), rainfall, sunshine, relative humidity, solar radiation intensity, sea level pressure and wind speed, etc. were detailed (how much change between before 2000s’and after the 2000s’) studied in these areas. These are the main drivers that influence the vulnerability dimensions resulting in livelihood strategies and access to food, water, agricultural practices, income and overall livelihood, and leads to a vicious cycle of poverty. The study helps to understand the impacts of climate change, and natural disaster-related threats in the northern char area. Also suggested that if providing necessary institutional and organizational supports for strengthening the livelihood capitals, assets, and strategy to combat or mitigate impacts of climate change aspects in Bangladesh.SAARC J. Agric., 19(2): 317-330 (2021)